Deepening the Basis of Rural Resource Management: Proceedings of a Workshop - Loevinsohn, Michael E.; Guijt, Irene; Berdegué, Julio A. (International Service for National Agricultural Research, 2000)
As forces transform the conditions of agriculture and rural resource management, on global and on more local scales, farmers increasingly face decisions for which their experience provides limited guidance. The capacity of rural people to adapt their decisions about resources, collectively, jointly or individually managed, to changed circumstances is key to any meaningful sense of sustainable development. The workshop, Deepening the Basis of Rural Resource Management, gave researchers working in diverse situations and with resources of different types (natural, human and economic) an opportunity to discuss their experiences and explore cross-cutting methodological, practical and institutional issues with a view to bringing about a more literate and equitable management that better meets people's goals.